Bispecific antibodies against the hepatitis C virus E1E2 envelope glycoprotein - Laura Radić; Anna Offersgaard; Tereza Kadavá; Ian Zon; Joan Capella-Pujol; Fabian Mulder; Sylvie Koekkoek; Vera Spek; Ana Chumbe; Jens Bukh; Marit J. van Gils; Rogier W. Sanders; et al. (Proceedings of the National Academy of Sciences, 2025)
Hepatitis C virus (HCV) currently causes about one million infections and 240,000 deaths worldwide each year. To reach the goal set by the World Health Organization of global HCV elimination by 2030, it is critical to develop a prophylactic vaccine. Broadly neutralizing antibodies (bNAbs) target the E1E2 envelope glycoproteins on the viral surface, can neutralize a broad range of the highly diverse circulating HCV strains, and are essential tools to inform vaccine design. However, bNAbs targeting a single E1E2 epitope might be limited in neutralization breadth, which can be enhanced by using combinations of bNAbs that target different envelope epitopes. We have generated 60 immunoglobulin G (IgG)-like bispecific antibodies (bsAbs) that can simultaneously target two distinct epitopes on E1E2. We combine non- or partially overlapping E1E2 specificities into three types of bsAbs, each containing a different hinge length. The majority of bsAbs shows retained or increased potency and breadth against a diverse panel of HCV pseudoparticles and HCV produced in cell culture compared to monospecific and cocktail controls. Additionally, we demonstrate that changes in the hinge length of bsAbs can alter the binding stoichiometry to E1E2. These results provide insights into the binding modes and the role of avidity in bivalent targeting of diverse E1E2 epitopes.This study illustrates how potential cooperative effects of HCV bNAbs can be utilized by strategically designing bispecific constructs. These HCV bsAbs can guide vaccine development and unlock novel therapeutic and prophylactic strategies against HCV and other (flavi)viruses.